Spiritual Tourism: A Grounded Theory Approach - Sudiarta, Made; Bratayasa, I Wayan; Subadra, I Nengah; Endrayani (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
Spiritual tourism is a rapid growing segment of the travel industry that focuses on journeys aiming at fostering personal growth, self-discovery, and connection with sacred or transcendent experiences. This article explores the evolution, current trends, and future directions of spiritual tourism through a qualitative, grounded theory approach. Historically rooted in ancient pilgrimages and religious practices, spiritual tourism has evolved into a blend of traditional and contemporary spiritual pursuits, influenced by globalization and the rise of new age spirituality. Using Bali as a case study, the article highlights the island’s emergence as a global center for spiritual tourism which driven by its unique cultural and natural offerings. However, challenges such as cultural commodification and sustainability concerns are also discussed. The article identifies gaps in the literature, including the need for deeper qualitative research and the exploration of technology’s role in shaping spiritual tourism experiences. Ultimately, spiritual tourism offers significant potential for fostering cross-cultural understanding and sustainable development